2023
DOI: 10.1039/d2cc05370e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis strategies to control the Al distribution in zeolites: thermodynamic and kinetic aspects

Abstract: The activity and selectivity of acid-catalyzed chemistry is highly dependent on the Brønsted and Lewis acid sites generated by Al substitutions in a zeolite framework with the desired pore architecture....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 131 publications
(246 reference statements)
0
20
0
Order By: Relevance
“…Given that positive charges on these OSDAs compensate for the negatively charged aluminosilicate framework, it is natural to assume that the OSDAs can control the location of Al. [15][16][17] Although kinetics 14 and the presence of alkali metal cations 18 play major roles, a general agreement for experimental and computational studies is that the positive charge introduced by OSDAs is in proximity to Al in zeolites. 10,13,17,[19][20][21] However, a general understanding of factors contributing to the strength of this Al site-directing ability for different OSDAs is still lacking.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Given that positive charges on these OSDAs compensate for the negatively charged aluminosilicate framework, it is natural to assume that the OSDAs can control the location of Al. [15][16][17] Although kinetics 14 and the presence of alkali metal cations 18 play major roles, a general agreement for experimental and computational studies is that the positive charge introduced by OSDAs is in proximity to Al in zeolites. 10,13,17,[19][20][21] However, a general understanding of factors contributing to the strength of this Al site-directing ability for different OSDAs is still lacking.…”
mentioning
confidence: 91%
“…7 Indeed, several studies have demonstrated that zeolite catalysts with varying Al distributions can exhibit different catalytic behaviors. [8][9][10][11][12][13][14] An intuitive strategy to control the location of Al employs organic structure-directing agents (OSDAs). [15][16][17] OSDAs are generally organics that fit into the internal space of zeolite structures through van der Waals interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the topic of Si, Al ordering in a zeolite is a topic widely studied, as well as the role of OSDAs in the synthesis of zeolites, ,,− the reasons why (or if) the aluminum contributes to stabilize such a zeolite phase is a less explored aspect, and this is the aim of the present study. Following the idea of our previous work regarding the roles of fluoride and aluminum as SDAs in the synthesis of zeolites, we now try to compare the role of aluminum and fluoride on the synthesis of recently synthesized aluminosilicate zeolites PST-21 (PWO), PST-22 (PWW), and ERS-7 (ESV) by selecting certain specific cases in which different zeolites are obtained using the same OSDA when the synthesis gel has a silicate or aluminosilicate chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…65 As a result, significant effort has been dedicated to understanding the means by which to intentionally synthesize paired Al zeolites. The influence of kinetic factors, [66][67] Si source, 68 Al Source, 68 structure directing agents (SDA) [69][70] have all been investigated. The cations present in the SDAs that balance the charge of the Al 3+ , plays a role in Al siting within the zeolite.…”
mentioning
confidence: 99%